2020
DOI: 10.31236/osf.io/gq78r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of signposting and group support pathways on a community-based physical activity intervention grounded in motivational interviewing

Abstract: Background: Brief advice is recommended to increase physical activity (PA) within primary care. This study assessed change in PA levels and mental wellbeing after a motivational interviewing (MI) community-based PA intervention and the impact of signposting [SP] and Social Action [SA] (i.e. weekly group support) pathways. Methods: Participants (n=2084) took part in a community-based, primary care PA programme using MI techniques. Self-reported PA and mental wellbeing data were collected at baseline (following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…It could be that walking did not continually improve as more intensive PA displaced it over time, increasing overall improvements. Hardcastle et al 40 also reported significant changes in walking from baseline at six and 18-months, but is unclear if this plateaued from 12-weeks as found in the present study. Overall, PA levels were improved such that participants would be classified as having 'high' activity levels after 12-weeks, and this was maintained post six-months though without further improvement.…”
Section: What Is Already Known On This Topicsupporting
confidence: 47%
See 2 more Smart Citations
“…It could be that walking did not continually improve as more intensive PA displaced it over time, increasing overall improvements. Hardcastle et al 40 also reported significant changes in walking from baseline at six and 18-months, but is unclear if this plateaued from 12-weeks as found in the present study. Overall, PA levels were improved such that participants would be classified as having 'high' activity levels after 12-weeks, and this was maintained post six-months though without further improvement.…”
Section: What Is Already Known On This Topicsupporting
confidence: 47%
“…MI is a client centred direct approach to increase, guide, elicit, and strengthen intrinsic motivation to change, while exploring and resolving ambivalence 7,8 . MI was seen as an alternative to more directive and confrontational counselling 9 with client-cantered principles and techniques 10 . MI has been used to promote positive behaviour change in a number of domains and is one of few theory based interventions supported by evidence 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health care professional should be able to sufficiently explain the importance of strength and strength training. Ideally, they will also be able to direct their patient to a qualified clinical exercise physiologist, one with specific expertise that is matched to the ability of their patient [ 48 ]. However previous research confirms a lack of knowledge and confidence in this space to be a major barrier in doing so [ 46 ].…”
Section: Discussionmentioning
confidence: 99%